2019
DOI: 10.1177/1526602819892557
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Repair Using a 7-Branch Stent-Graft for a Thoracoabdominal Aortic Aneurysm With Variant Renovisceral Artery Anatomy

Abstract: Purpose: To present a case of endovascular repair using a custom-made 7-branch stent-graft for a thoracoabdominal aortic aneurysm (TAAA) in a patient with variations in the renovisceral artery anatomy. Case Report: A 70-year-old asymptomatic man presented with a 60-mm-diameter type IV TAAA. Due to severe coronary artery disease, an endovascular approach was elected. In the preoperative computed tomography angiography (CTA) scans, variations in the renovisceral artery anatomy included the common hepatic and spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Nevertheless, the anatomical feasibility of off-the-shelf stent-grafts has been demonstrated to be quite limited, in part due to variations of renal and visceral anatomy. [10][11][12] Conversely, patient-specific devices have the potential to address different anatomical configurations, such as the one presented in the current case report, 4 which reiterates the importance of continued utilization of such devices instead of a complete and exclusive transition to off-the-shelf devices.…”
Section: Endovascular Repair Of Abdominal Aortic Aneurysms (Evar)supporting
confidence: 58%
See 2 more Smart Citations
“…Nevertheless, the anatomical feasibility of off-the-shelf stent-grafts has been demonstrated to be quite limited, in part due to variations of renal and visceral anatomy. [10][11][12] Conversely, patient-specific devices have the potential to address different anatomical configurations, such as the one presented in the current case report, 4 which reiterates the importance of continued utilization of such devices instead of a complete and exclusive transition to off-the-shelf devices.…”
Section: Endovascular Repair Of Abdominal Aortic Aneurysms (Evar)supporting
confidence: 58%
“…13,14 Moreover, the ability to select branches or fenestrations can certainly be utilized to accommodate a wider variety of anatomies, thus facilitating the procedure based on the specific anatomy of the patient being treated. In this case, particularly, as pointed by the authors, 4 having branches instead of fenestrations was helpful during the procedure as their use provided additional space for catheter/wire manipulation into target vessels. Additionally, branches tend to have a more "forgiving" nature compared with fenestrations, which should be deployed precisely in apposition with their target vessels.…”
Section: Endovascular Repair Of Abdominal Aortic Aneurysms (Evar)mentioning
confidence: 69%
See 1 more Smart Citation
“…Technical experience and improved device design over time have allowed physicians to overcome multiple branches. Most recently, Eleshra et al [5] reported successful management of a patient with variant visceral vessel anatomy (bilateral double renal arteries with both common hepatic and splenic arteries originating from the aorta) with a stent graft with seven…”
Section: Introductionmentioning
confidence: 99%
“…However, follow-up examinations through 5 years will continue to assess the long-term results. Up to 7 branches have been described in case of variants of visceral arteries [176]. Physician-modified fenestrated stent grafts (PMSGs) are a useful option for urgent or semiurgent treatment of complex abdominal aortic aneurysms.…”
Section: Novel Strategiesmentioning
confidence: 99%